2005
DOI: 10.1007/s10571-005-8473-2
|View full text |Cite
|
Sign up to set email alerts
|

The Postnatal Development of the Cerebellum— A fMRI and Silver Study

Abstract: The aim of this study was to evaluate the postnatal development of the cerebella of the pig and to compare this with the activation of the fMRI. The cells in the cerebella were studied by silver technique and the activation of the fMRI in the cerebella was initiated by flexion and extension of the hind paw. Our results showed an increase of the branching of the cells of the cerebellar cortex postnatally, coordinated with registration of fMRI active sites in the cerebella at 6-month postnatal. We concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This method is used to make inferences about the effects of the stimuli by decomposing data into effects and errors, and computes statistical maps related to the effects of the stimuli (see Monti 2011 for principles). This kind of study is widely used in human and non-human primates, but due to a required subjects's involvement, typical fMRI activation paradigms have only been used in a few studies in large animals such as pigs or sheep (Fang et al 2005b, Fang et al 2005c, Fang et al 2006, Opdam et al 2002. Due to the constraints mentioned above (see 2.1), this kind of experimental paradigm will not be discussed further in this chapter.…”
Section: Typical Activation Studies: Block Designsmentioning
confidence: 99%
“…This method is used to make inferences about the effects of the stimuli by decomposing data into effects and errors, and computes statistical maps related to the effects of the stimuli (see Monti 2011 for principles). This kind of study is widely used in human and non-human primates, but due to a required subjects's involvement, typical fMRI activation paradigms have only been used in a few studies in large animals such as pigs or sheep (Fang et al 2005b, Fang et al 2005c, Fang et al 2006, Opdam et al 2002. Due to the constraints mentioned above (see 2.1), this kind of experimental paradigm will not be discussed further in this chapter.…”
Section: Typical Activation Studies: Block Designsmentioning
confidence: 99%
“…Pond et al 1969Pond et al , 1990Dobbing & Sands, 1979;Hall & Haworth, 1987;Yue et al 1997;David & Grongnet, 2001;Raghupathi & Margulies, 2002;Bauer et al 2004). Several studies have shown that the cellular components of the pig cerebellum, as in humans, are not fully differentiated at birth (Dickerson & Dobbing, 1966a,b;Merat & Dickerson, 1973;Badger & Tumbleson, 1975;Pond et al 2000;Fang et al 2005). Using the increase in DNA and cholesterol content as an expression for cell differentiation and myelination it has become clear than different parts and structures of the brain develop at unique rates (Dickerson & Dobbing, 1966a;Badger & Tumbleson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The structural development of the pig cerebellum has been documented in several studies, both prenatally (e.g. Larsell, 1954;Done & Hebert, 1968) and postnatally (Fang et al 2005). However, no data are available regarding the quantitative development of specific cellular components in the pig cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellum is very vulnerable to injury and impaired growth ( 12 ). As the basic architecture of the cerebellar cortex is comparable between pigs and humans ( 15 ), we aimed to evaluate the apoptotic effect of continuous intravenous fentanyl on the cerebellum in healthy newborn pigs.…”
Section: Introductionmentioning
confidence: 99%